Regarding the right to consular assistance of citizens of the European Union not represented in third States - Moreiro González, Carlos J. (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The right to consular protection of the citizens of the European Union without representation of their diplomatic or consular authorities in a third State was enshrined in the Treaty of Maastricht ,but its legal implementation took place later.The intergovernmental decisions that initially regulated its exercise were replaced by supranational law,currently in force, that grants better legal guarantees to the citizens.Recently,the reform of said regulatory framework has begun to improve the scope of implementation and the protection of this right by public authorities.